Who Spends Too Much Time Online? : Associated Factors of Internet Addiction Among International College Students in the United States - Koo, Katie; Nyunt, Gudrun; Wang, Boshi (Journal of International Students, 2021)
This study investigated the relation between Internet addiction and several associated factors (mental health, academic performance, socioeconomic status, self-esteem, demographic characteristics) for international students in the United States. One hundred and fifty-seven international students at a U.S. university completed five questionnaires: an Internet usage behavior questionnaire, an Internet addiction scale, a self-esteem inventory, a mental health inventory, and a demographic questionnaire. Data were analyzed using SPSS to examine the relation between Internet addiction and associated factors. The results indicated that male students who speak English as a second language and who are not religious are more likely to develop Internet addiction. Academic performance and socioeconomic status were found to be positive predictors of Internet addiction, and mental health and self-esteem were found to be negative predictors of Internet addiction. The relations between other associated factors were also examined.